“Fun, disturbing and ultimately forgettable”? : Notes on the Royal Court Theatre Production of Martin McDonagh’s Hangmen - Pilný, Ondřej (Hungarian Journal of English and American Studies, 2020)
The essay compares the reflections of a translator on the text of Martin McDonagh’s latest play, Hangmen (2015), with the impact of its first production by the Royal Court Theatre in London. It considers the response of multiple reviewers and of the Royal Court and West End audiences and argues that while this may be the first work by McDonagh that features a serious concern—this being the practice of capital punishment and its effect on society—the Royal Court production unduly obscured this aspect of the drama by mostly playing it only for the laughs. (OP)